2023
DOI: 10.1002/cctc.202201579
|View full text |Cite
|
Sign up to set email alerts
|

Activity Regulation of Fenton/Fenton‐like Reactions in Single‐Atom Catalysis

Abstract: On the one hand, Fenton‐like reactions are common side reactions in electrocatalytic oxygen reduction reaction (ORR). The generated reactive oxygen species (ROS) could damage the active sites of single‐atom catalysts (SACs), thereby affecting the stability of the catalysts. On the other hand, the Fenton‐like reaction could generate radicals with strong oxidative properties, which could be used in the degradation of pollutants and tumor therapy. In this review, we summarize strategies to limit the occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 146 publications
0
3
0
Order By: Relevance
“…[97] destroy its coordination environments, thus the activity of Fe SACs-based electrocatalysts will gradually decrease or even deactivate. [100] Therefore, in the catalytic sensing system involving * OH radicals, it is a simple and practical strategy to regulate the central metal elements with high chemical activity and strong tolerance. CoÀ N x , which is similar in structure to the natural metalloenzymes, is much more stable in this respect and can be used as one of the best choices in some environments which involve * OH.…”
Section: Metal Centers Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[97] destroy its coordination environments, thus the activity of Fe SACs-based electrocatalysts will gradually decrease or even deactivate. [100] Therefore, in the catalytic sensing system involving * OH radicals, it is a simple and practical strategy to regulate the central metal elements with high chemical activity and strong tolerance. CoÀ N x , which is similar in structure to the natural metalloenzymes, is much more stable in this respect and can be used as one of the best choices in some environments which involve * OH.…”
Section: Metal Centers Regulationmentioning
confidence: 99%
“…As expected, Fe SACs owns excellent sensitivity and exceptional selectivity for electrochemical H 2 O 2 sensing, and the detection limit can reach nM level (Figure 8a). [89] Some studies have shown that the reactive oxygen species (ROS) can attack the Fe atom sites or destroy its coordination environments, thus the activity of Fe SACs‐based electrocatalysts will gradually decrease or even deactivate [100] . Therefore, in the catalytic sensing system involving ⋅OH radicals, it is a simple and practical strategy to regulate the central metal elements with high chemical activity and strong tolerance.…”
Section: Improving Catalytic Sensing Performance Via Structural Regul...mentioning
confidence: 99%
“…have also demonstrated the ability to H 2 O 2 to •OH through Fenton-type reactions. [92] Recently, Co-SAs@NC with Co-N 4 as the center showed excellent Fenton-like activity, producing enough O 2…”
Section: Endogenous Stimulus Responsivementioning
confidence: 99%